Մեծ եղեռնը վերապրած Ալխոր Շուշանյանի հուշապատումը - Ավագյան, Ինգա
Այս հուշապատումներից մեկն է գրող եւ բանաստեղծ Խորեն Ալեքսանյանի (ստեղծագործել է Ալխոր Շուշանյան գրական կեղծանվան ներքո) «Մանկությունս. թուրքական արշավանքների տարիներին» խորագրով անտիպ հուշապատումը, որը ընթերցողին ներկայացվում է սույն հրապարակումով: Переживший Армянский геноцид Хорен Алексанян - писатель, который творил под псевдонимом Алхор Шушанян, родился в 1914г. в Ширакском селе Казанчи - ныне Меграшат. Он творил в разных жанрах и направлениях: поэзия, повесть, на армянский язык переводил известных немецких и английских авторов. Пережив два турецких нашествия (1918 и 1920 гг.) он получает образование, преподает в сельской школе, возглавляет одну из школ района, но во время Великой Отечественной войны он попадает в плен и после победы, боясь сталинских репрессий, он решает переправиться через океан в США. The survivor of the Armenian genocide Khoren Aleksanyan - a writer who worked under the pseudonym Alhor Shushanyan, was born in 1914 in Shirak village Kazanchi - now Megrashat. He worked in different genres and directions: poetry, story, translated famous German and English authors’ writings into Armenian. Having survived two Turkish invasions (1918 and 1920), he gets an education, teaches at a rural school, heads up one of the schools in the district, but during the World War II war he is captured prisoner and after the victory of the Soviet Union, fearing Stalinist repression, he decides to cross over across the ocean to the USA.
Keywords: Armenian Genocide (1915); Literature